ChemInform Abstract: Palladium‐Catalyzed Synthesis of Aromatic Ketones and Isoindolobenzimidazoles via Selective Aromatic C—H Bond Acylation. Issue 30 (4th July 2013) - Lu, Juyou; Zhang, Hao; Chen, Xiaowu; Liu, Hongxia; Jiang, Yuyang; Fu, Hua
Abstract An efficient synthesis of aromatic ketones (III) and isoindolobenzimidazoles (IX) via selective aromatic C—H activation is described.